“Enhancing Students’ Artistic Competencies through Drawing in Visual Arts Education” - Rustamov Axtam Muxtorovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the role of drawing in enhancing students’ artistic competencies in visual arts education. It examines how structured drawing activities contribute to the development of creative thinking, technical skills, visual literacy, and cultural awareness. The study also highlights the importance of integrating traditional motifs and national values to foster students’ understanding of cultural heritage while promoting innovation and personal expression.